Análisis de los procesos de planeación y ejecución de la construcción de la presa en RCC del Proyecto Hidroeléctrico Pirrís como experiencia para proyectos similares - Gamboa-Solís, Arturo José (Instituto Tecnológico de Costa Rica, 2011)
This document seeks to identify the processes leading to consider in the initial planning for the placement of the RCC in the construction of a dam, so as to ensure the coordination and control of production plants, transport of materials, installation of temporary works and implementation of major civil works that complement the construction of a dam RCC (roller compacted concrete). To meet this objective, analyzed and made photographic records, programs work and shop drawings that support the explanation of the processes that have been established, based on experience (in advance) and during construction of the dam the "Pirrís Hydroelectric Project" (PH PIRRÍS) conducted by the Instituto Costarricense de Electricidad (ICE). We identified the main processes and sub processes during the execution of an RCC dam, basic work schemes in the implementation of production processes, procedures and working models of the major works that make the dam, and finally the mitigation actions by consider a work of this kind, with the involvement of adverse weather events like floods. It concludes with a series of recommendations to serve as reference for future projects that the Instituto Costarricense de Electricidad develop under construction and design features similar to those developed here.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2011.
Keywords: Vertedor; Contrapresa; Concreto compactado con rodillo; Descarga de fondo; Toma de agua